DINAMIKA KONFLIK AGRARIA DI INDONESIA : FAKTOR PENYEBAB DAN DAMPAKNYA - Petrus Atong (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2025)
Agrarian conflicts in Indonesia have become a chronic issue involving various sectors such as plantations, forestry, infrastructure, and property. In 2023, there were 241 recorded agrarian conflicts in Indonesia, involving the seizure of 638,188 hectares of land, which included agricultural areas, customary territories, fishing zones, and community settlements, affecting 135,608 households. Moreover, 110 conflicts resulted in 608 victims among land rights defenders due to repressive actions in agrarian conflict zones. These figures place Indonesia at the top of the list among six other Asian countries, including India, Cambodia, the Philippines, Bangladesh, and Nepal. The conflicts are not only caused by overlapping policies and land control by large corporations but also by maladministration practices and resource exploitation that neglect local community rights. The impacts of agrarian conflicts are extensive, encompassing social, economic, and cultural losses, as well as human rights violations. Furthermore, repressive actions by authorities and policy imbalances often exacerbate the situation. This study employs a descriptive qualitative approach with literature review methods to analyze the causes and impacts of agrarian conflicts. The findings highlight the need for a fair, inclusive, and sustainable approach through agrarian reform to address these issues and promote equitable economic distribution.